2021
DOI: 10.1021/acs.langmuir.0c03370
|View full text |Cite
|
Sign up to set email alerts
|

Nematic Phase of Plate-like Semicrystalline Block Copolymer Single Crystals in Solution Studied by Small-Angle X-Ray Scattering

Abstract: Crystalline block copolymers have been used to prepare plate-like colloidal systems with well-controlled size, shape, and size distribution. The isotropic-to-nematic (I–N) phase transition of the novel plate-like colloidal particle suspensions has been reported previously. In this work, we focus on the characterization of the solution structure of the crystals and the N-phase using small- and ultrasmall-angle X-ray scattering techniques (SAXS/USAXS). The system has polystyrene-block-poly­(l-lactide) (PS-b-PLLA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…He et al studied the LC phase behaviors in the suspension of a series of PLLA-b-PS BCPSCs and PLLA/PLLA-b-PS HSCs. 91,173,174 They found that the critical volume fraction of phase transition was obviously smaller than the theoretical value, which resulted from the lateral attraction between the lamellae and external gravity. They also determined the critical volume fraction of the phase transition as a function of the size of the crystals and verified the size-dependence via the self-seeding procedure to obtain lamellae of different sizes.…”
Section: Functionalization and Properties Of Single Crsytals And 2d A...mentioning
confidence: 98%
See 1 more Smart Citation
“…He et al studied the LC phase behaviors in the suspension of a series of PLLA-b-PS BCPSCs and PLLA/PLLA-b-PS HSCs. 91,173,174 They found that the critical volume fraction of phase transition was obviously smaller than the theoretical value, which resulted from the lateral attraction between the lamellae and external gravity. They also determined the critical volume fraction of the phase transition as a function of the size of the crystals and verified the size-dependence via the self-seeding procedure to obtain lamellae of different sizes.…”
Section: Functionalization and Properties Of Single Crsytals And 2d A...mentioning
confidence: 98%
“…Nanocomposite hydrogels with platelet micelles showed better mechanical properties, and a self‐healing ability between two freshly cut surfaces of the same gels, which is promising for use in living organisms. He et al studied the LC phase behaviors in the suspension of a series of PLLA‐ b ‐PS BCPSCs and PLLA/PLLA‐ b ‐PS HSCs 91,173,174 . They found that the critical volume fraction of phase transition was obviously smaller than the theoretical value, which resulted from the lateral attraction between the lamellae and external gravity.…”
Section: Functionalization and Properties Of Single Crsytals And 2d A...mentioning
confidence: 99%